Ethnobotany, phytochemistry, pharmacology and toxicity of Hagenia abyssinica (Bruce) J.F.Gmel.: a review - Shi, Guohui; Ni, Linlin; Zhang, Yang; Qu, Zhizi; Kong, Xiaoni; Zhou, Honglei; Xu, Yan (Frontiers in Pharmacology, 2025)
Hagenia abyssinica: (Bruce) J.F.Gmel. (H. abyssinica), commonly known as “kosso,” is a prevalent phytomedicine addressing aliments across Ethiopia. Traditionally, it is used to treat fever, abdominal pain, respiratory illnesses, intestinal parasitic infections, wound healing, and cancer. Current research has revealed its anthelmintic, antimicrobial, antihyperglycemic, antidyslipidemic, antidiarrheal, and antioxidant activities. These pharmacological properties might be attributed to the presence of secondary metabolites, such as terpenoids, flavonoids, and phenols. Its crude extract is safe in vivo at doses less than 2,000 mg/kg, but larger doses can cause damage to the optic nerve. Although significant research findings are available, challenges remain. This paper provides a comprehensive review of research findings, identifying gaps in mechanistic studies and standardized toxicology assessments. Future priorities include applying ConPhyMP guidelines for extract characterization and integrating traditional knowledge with biodiversity conservation.